Relationship of Knowledge Level on Medicine Use in Hypertension Patients in the Puskesmas Sungai Tabuk Area - Latif, Akmal; Kurniawati, Darini; Dona, Sismeri (Journal of Advances in Medicine and Pharmaceutical Sciences, 2022)
Hypertension or high blood pressure is a condition in which a person experiences an increase in blood pressure if the systolic blood pressure is more than or equal to 140 mmHg and the diastolic pressure is more than or equal to 90 mmHg. In 2018 the Province of South Kalimantan was ranked first at 44.1% at the age of >18 years, which means that there was a significant increase in the number of people with hypertension in the Province of South Kalimantan. The purpose of this study was to determine the relationship between the level of knowledge and the use of drugs in hypertensive patients in the Sungai Tabuk 3 Community Health Center. The method used was a csoss-sectional or cross-sectional design. The sample is the people who live in the Sungai Tabuk Health Center area with a sample of 60 people with the Consecutive Sampling sampling technique. Using a questionnaire as a measuring tool. Data were analyzed by Spearman rho test with 95% confidence level. The result of the level of knowledge of respondents in the good category is 41 people (68.33%) with rational use of antihypertensive drugs as many as 33 people (50.00%). The results of the Spearman rho test on the relationship between the level of knowledge and the use of antihypertensive drugs obtained a significance value of 0.000 (<0.05), the correlation coefficient was 0.532 with a positive correlation direction. There is a relationship between the level of knowledge and the use of antihypertensive drugs in the community living in the Sungai Tabuk 3 Community Health Center.